CHET TILINI O'QITISH METODIKASIDA ZAMONAVIY METODLAR («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article talks about the methodology of foreign language teaching, the history of its development as a science, the types of modern methods used in the methodology of foreign language teaching and their use.
Keywords: methodology, innovation, foreign language, communication, skills, competence, intercultural communication.